2012
DOI: 10.1371/journal.pone.0050935
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Is a Target of MicroRNA-16 in Human Hepatoma Cells

Abstract: Cyclooxygenase-2 (COX-2) expression has been detected in human hepatoma cell lines and in human hepatocellular carcinoma (HCC); however, the contribution of COX-2 to the development of HCC remains controversial. COX-2 expression is higher in the non-tumoral tissue and inversely correlates with the differentiation grade of the tumor. COX-2 expression depends on the interplay between different cellular pathways involving both transcriptional and post-transcriptional regulation. The aim of this work was to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 57 publications
0
30
0
1
Order By: Relevance
“…58 Interestingly, several of the tumor types which, in addition to BC and GC, show ErbB-2 gene amplification or protein overexpression, display low levels of miR-16. 5965 Given that miR-16 was found to act as a tumor suppressor in these cancers, 5965 our findings raise the exciting possibility that ErbB-2 inhibition of miR-16 expression may be a common mechanism underlying ErbB-2-driven cancer growth. TZ has been found to regulate the expression of other miRNAs, which mediate its antiproliferative effects in BC.…”
Section: Discussionmentioning
confidence: 86%
“…58 Interestingly, several of the tumor types which, in addition to BC and GC, show ErbB-2 gene amplification or protein overexpression, display low levels of miR-16. 5965 Given that miR-16 was found to act as a tumor suppressor in these cancers, 5965 our findings raise the exciting possibility that ErbB-2 inhibition of miR-16 expression may be a common mechanism underlying ErbB-2-driven cancer growth. TZ has been found to regulate the expression of other miRNAs, which mediate its antiproliferative effects in BC.…”
Section: Discussionmentioning
confidence: 86%
“…Cytoplasmic HuR can also bind to miR-16 and downregulate it. (This mechanism may also exist in hepatoma [5]). In the same research, the mRNA of Bcl-2 and VEGF, which are also the targets of miR-16, showed to contain ARE too and could be protected from miR-16 mediated decay by HuR.…”
Section: • • Colorectal Cancermentioning
confidence: 92%
“…COX-2 expression depends on the interplay between different cellular pathways involving both transcriptional and post-transcriptional regulation (Agra Andrieu et al, 2012). Normally absent in most cells, COX-2 (PTGS2) expression is rapidly induced by proinflammatory and growth-associated stimuli.…”
Section: Introductionmentioning
confidence: 99%